The use of supplementary materials for teaching children in EFL classes research done in order to archive the bachelor’s degree in teaching english as a foreign language - Cabrera Rodríguez, Meri del Carmen (2012)
This research work refers to the use of supplementary materials for teaching children in EFL classes, at elementary schools, especially in the fourth, fifth and sixth grades. The focus of this thesis was to determine and analyze the types of supplementary materials more frequently used to teach English as a foreign language to young children, the research took place at a private school in Azogues. Data was collected from ten observations in each class and surveys for further analysis. During the study, observation sheets were filled out. In addition to the observation, a student’s survey was given to 60 students chosen randomly which included six questions related to the influence, use, and preference of the supplementary materials. Also a teacher’s survey was given to reveal the teacher’s belief about using supplementary materials. Regarding the findings of the current study, the whiteboard was more frequently used than the other tools. Finally, the results of the present study will enrich our understanding of the importance of the use of supplementary materials to improve the students’ interest towards English as a foreign language.